Osteoporosis and alzheimer pathology: Role of cellular stress response and hormetic redox signaling in aging and bone remodeling - Cornelius, Carolin; Koverech, Guido; Crupi, Rosalia; Di Paola, Rosanna; Koverech, Angela; Lodato, Francesca; Scuto, Maria; Salinaro, Angela T.; Cuzzocrea, Salvatore; Calabrese, Edward J.; Calabrese, Vittorio (Frontiers in Pharmacology, 2014)
Alzheimer’s disease (AD) as well as osteoporosis are multifactorial progressive degenerative disorders characterized by low parenchymal density and microarchitectural deterioration of tissue. Though not referred to as one of the major complications of AD, osteoporosis and hip fracture are commonly observed in patients with AD, however, the mechanisms underlying this association remain poorly understood. Reactive oxygen species (ROS) are generally recognized as intracellular redox signaling molecules involved in the regulation of bone metabolism, including receptor activator of nuclear factor-kB ligand (RANKL)-dependent osteoclast differentiation, but they also have cytotoxic effects that include peroxidation of lipids and oxidative damage to proteins and DNA. ROS formation, which is positively implicated in cellular stress response mechanisms, is a highly regulated process controlled by a complex network of intracellular signaling pathways which regulate life span across species including vitagenes which are genes involved in preserving cellular homeostasis during stressful conditions. Vitagenes encode for heat shock proteins (Hsp) Hsp32, Hsp70, the thioredoxin and the sirtuin protein systems. Dietary antioxidants, have recently been demonstrated to be neuroprotective through the activation of hormetic pathways, including vitagenes. The hormetic dose–response, has the potential to affect significantly the design of pre-clinical studies and clinical trials as well as strategies for optimal patient dosing in the treatment of numerous diseases. Given the broad cytoprotective properties of the heat shock response there is now strong interest in discovering and developing pharmacological agents capable of inducing stress responses. Here we focus on possible signaling mechanisms involved in bone remodeling and activation of vitagenes resulting in enhanced defense against energy and stress resistance homeostasis dysruption with consequent impact on aging processes.